A modular, cost-effective, versatile, open-source operant box solution for long-term miniscope imaging, 3D tracking, and deep learning behavioral analysis - Nicholas J. Beacher; Jessica Y. Kuo; Miranda Targum; Michael Wang; Kayden A. Washington; Giovanna Barbera; Da-Ting Lin (MethodsX, 2024)
In this procedure we have included an open-source method for a customized operant chamber optimized for long-term miniature microscope (miniscope) recordings. • The miniscope box is designed to function with custom or typical med-associates style accessories (e.g., houselights, levers, etc.). • The majority of parts can be directly purchased which minimizes the need for skilled and time-consuming labor. • We include designs and estimated pricing for a single box but it is recommended to build these in larger batches to efficiently utilize bulk ordering of certain components.